2016
DOI: 10.3847/2041-8205/820/2/l40
|View full text |Cite
|
Sign up to set email alerts
|

RINGED SUBSTRUCTURE AND A GAP AT 1 au IN THE NEAREST PROTOPLANETARY DISK

Abstract: We present long-baseline Atacama Large Millimeter/submillimeter Array (ALMA) observations of the 870 µm continuum emission from the nearest gas-rich protoplanetary disk, around TW Hya, that trace millimeter-sized particles down to spatial scales as small as 1 AU (20 mas). These data reveal a series of concentric ring-shaped substructures in the form of bright zones and narrow dark annuli (1-6 AU) with modest contrasts (5-30%). We associate these features with concentrations of solids that have had their inward… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
602
1
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 547 publications
(664 citation statements)
references
References 57 publications
39
602
1
22
Order By: Relevance
“…As our models assume p=3.5, an increase in the maximum dust grain size by a factor of ∼75, say, from 1 mm to 10 cm, could explain this drop in flux. This is borne out by a number of studies that have found cavities, gaps, spiral arms, and other asymmetries in Class II disks that may indicate the presence of planets (Isella et al 2010Andrews et al 2011Andrews et al , 2016Casassus et al 2013; Weidenschilling 1977). We find that our Class I disks, on average, are more massive than the Taurus Class II disks, likely due to dust grain processing hiding matter in larger bodies in the older Class II disks.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 52%
“…As our models assume p=3.5, an increase in the maximum dust grain size by a factor of ∼75, say, from 1 mm to 10 cm, could explain this drop in flux. This is borne out by a number of studies that have found cavities, gaps, spiral arms, and other asymmetries in Class II disks that may indicate the presence of planets (Isella et al 2010Andrews et al 2011Andrews et al , 2016Casassus et al 2013; Weidenschilling 1977). We find that our Class I disks, on average, are more massive than the Taurus Class II disks, likely due to dust grain processing hiding matter in larger bodies in the older Class II disks.…”
Section: Class I Versus Class Ii Disk Massesmentioning
confidence: 52%
“…see their Figure 11). Hence, the dark annulus detected by Andrews et al (2016) may indeed be the first stage of the dispersal phase of the TW Hya disc. Direct evidence of currently ongoing photoevaporation is provided by the detection of a few km/s blueshift in the profile of the [NeII] 12.8 µm line (Herczeg et al 2007;Pascucci & Sterzik 2009), which is well fit by both EUV and X-ray photoevapoaration models (Alexander 2008.…”
Section: Evidence Of X-ray Photoevaporation In Tw Hyamentioning
confidence: 99%
“…The ALMA observations together with the dip in the SED at mid-infrared wavelengths (Calvet et al 2002) suggest that the gap must be depleted of grains from µm to cm size. On that basis, Andrews et al (2016) argue against the dip being a consequence of changing solid properties at around the H2O snow-line. As an alternative, they suggest that a more detailed modeling of the ALMA data may show whether a young super-Earth may be responsible for dynamically carving the observed gap (e.g., Picogna & Kley 2015, Rosotti et al 2016.…”
Section: Gaps and Rings: The Alma Viewmentioning
confidence: 99%
See 2 more Smart Citations